Ficus deltoidea var. kunstleri extract administration in Hypercholesterolaemic, atherosclerotic rabbits: effects on organ function, morphology, and atherosclerosis development - Amirah Mohd Ariff,; Effat Omar,; Suhaila Muid,; Noor Alicezah Mohd Kasim,; Nor Hadiani Ismail,; Hapizah Nawawi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ficus deltoidea (FD) is used in traditional Malay medicine to treat various ailments and has been shown to be safe in toxicity studies. However, the information on the safety and efficacy of FD in the atherosclerosis-induced animal model is limited. This study aims to investigate the safety of FD var. kunstleri (FDK) extract on high cholesterol diet (HCD)-induced atherosclerotic rabbits and its efficacy in treating atherosclerosis. New Zealand White rabbits were randomly divided into two groups: G1 (1% HCD for 4 weeks) and G2 (1% HCD for 8 weeks). Each group was randomised into FDK700 (700 mg FDK/kg/day for G1 and G2), FDK800 (800 mg FDK/kg/day for G2), simvastatin (5 mg/kg/day) and placebo. The body weight, blood pressure, serum biochemistry and histopathological examination were obtained to assess any toxicity signs. Fasting lipid profile, soluble c-reactive protein (sCRP) level and atherosclerotic plaque formation were compared between treated and placebo groups to evaluate treatment efficacy. Results: No significant differences were observed in all safety parameters between the treated and placebo groups (p<0.05). FDK treatment did not show significant differences in all parameters evaluated in both treatment arms. In conclusion, FDK extract up to 800 mg/kg is safe for use in atherosclerotic rabbits. It has neutral effects on lipid profile, inflammation and atherosclerosis formation.